Prospects for the development of international tourism in Ukraine - Mekhovich, S. A.; Pererva, P. G. (Видавничий центр Київського національного університету культури і мистецтв, 2023)
It has been proven that the measures taken by Ukraine to stimulate international tourism and the visa-free regime have led to the improvement of a number of indicators: the share of citizens making international tourist trips has increased, the competitiveness of Ukraine's international tourism in the international ranking has increased. countries Ukraine ranks 9th in the world in the ranking of leading countries in international tourism.
Перспективи розвитку міжнародного туризму в Україні
Keywords: tourism industry; international business; development prospects; economy